A conceptual framework for measuring value creating Corporate Social Responsibility - Tobias Meurer; Michael Volkmann (Technische Hochschule Köln, Schmalenbach Institut für Wirtschaftswissenschaften, 2020)
The increasing public awareness of business related impacts on environmental and social well-being, be it positive or negative, are nowadays key drivers of corporate success. Internal and external business environments exert pressure and force transparency as well as responsible action in terms of resolving environmental and social impacts. In line with this, Porter and Kramer regard business behaviour that addresses societal needs and challenges, as the "new way to achieve economic success". However, whereas some companies "remain trapped in an out-dated approach to value creation" and restrict their CSR commitment to the compliance with governmental regulation, others proactively address stakeholder needs. By addressing these needs, companies can benefit from grasping the opportunity of enhanced cost efficiency and lowered risk or gaining competitive advantages through establishing unique value propositions, in a way that meets stakeholder demands. Apart from that, CSR performance can be seen as powerful tool to successfully influence stakeholder perceptions in terms of reputation, and thus an exceptional source of value creation. In addition to this, organisations can profit from win-win-win situations related to syncretic value creation by means of partnering with stakeholders. (...)
urn:nbn:de:hbz:832-epub4-15112
Keywords: 650; CSR; Measuring Corporate Social Responsibility; Value creating; Corporate Social Responsibility; Wertschöpfung